Complete removal of endocrine disrupting compound and toxic dye by visible light active porous g-C3N4/H-ZSM-5 nanocomposite. (February 2020) - Aanchal,; Barman, Sanghamitra; Basu, Soumen
Abstract: Photocatalytic degradation of toxic pollutants is an efficient technique to completely remove the toxic pollutants from water bodies. In the present investigation, photocatalytic degradation of pollutants was studied over porous g-C3 N4 /H-ZSM-5 nanocomposite under visible light irradiation. The composite g-C3 N4 /H-ZSM-5 was synthesized by mixing an aqueous solution of H-ZSM-5 zeolite (increases surface area and provides active sites for degradation) with melamine (precursor of g-C3 N4 ) for 10–12 h followed by calcinations at 550 °C. The photocatalyst was characterized by XRD, BET, HRTEM, FESEM, EDS and elemental mapping analysis. These techniques confirmed that, g-C3 N4 /H-ZSM-5 composite have layered and porous structure with uniform distribution of g-C3 N4 on H-ZSM-5 surface. The BET N2 adsorption-desorption analysis verified that the catalyst has high surface area (∼175 m 2 /g) having mesopores and micropores. The prepared catalyst was then used for the photodegradation of a model dye, Methylene Blue (MB) and an endocrine disrupting compound, Fipronil (FIP). Effects of various parameters such as pH, catalyst dose and scavengers were also studied. The % photocatalytic degradation of MB and FIP were around ∼92% and ∼84% with a high rate constants of 0.00997 and 0.00875 min −1, respectively. From the scavenger study, OH (hydroxyl radical) and radical was found to be the major reactive species for MB and FIP degradation. From these studies it is revealed that, the catalyst is visible active, easy to prepare and an efficient photocatalyst for toxic pollutant degradation. Graphical abstract: Image 1 Highlights: g-C3 N4 /H-ZSM-5 composite was synthesized by facile calcination method. Fipronil and Methylene blue were degraded to test the photocatalytic activity. Maximum photodegradation was obtained by optimizing reaction conditions. Scavenger study was performed to find the responsible species for degradation.